TEACHING ECONOMIC VALUES TO CHILDREN IN THE VILLAGE: INDEPENDENT KKN PROGRAM IN BUILDING ENTREPRENEURIAL CHARACTER FROM AN EARLY AGE IN GONGSOL VILLAGE - Fadillah , Intan Nur; Afandi, Ahmad (Journal of Social Comunity Services, 2024)
General Background: Entrepreneurship education for children is essential to foster economic understanding and business skills from an early age, particularly in rural areas where job opportunities are limited. Specific Background: In Gongsol Village, there is a lack of awareness among children regarding economic values and the potential of entrepreneurship as a sustainable career path. Knowledge Gap: Although entrepreneurship education for adults is common, programs tailored for children in rural areas remain scarce. Aims: This community service project aimed to introduce entrepreneurship concepts and develop entrepreneurial character in children, fostering motivation and practical skills for starting small businesses. Results: The program, which included educational sessions, practical demonstrations, and video documentation on creating simple products (e.g., stuffed tofu), significantly increased children's motivation to start a business, as evidenced by high participation rates and positive feedback on entrepreneurial knowledge and skills. Novelty: This initiative is among the first to provide structured entrepreneurship education specifically designed for young children in rural settings, combining theoretical and practical approaches. Implications: The program demonstrates that early entrepreneurial education can significantly enhance children's economic literacy and entrepreneurial mindset, potentially leading to greater entrepreneurial engagement in the future. Further research is needed to assess the long-term impact of such programs on children's business development and economic empowerment.